Food Safety Control as a Guarantee of Consumer Protection: Institutional Component - MYTNYK, Aliesia; LATYSHEVA, Viktoriia; VASECHKO, Lyudmyla; SHCHERBAKOVA, Nataliia; SEROHINA, Nataliia (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).15, 2022)
A serious challenge for modern society is the problem of ensuring food safety, which has reached the international scale. Despite the global scale of the food safety problem, its solution seems possible through the effective operation of relevant national institutions in the first place. The research objective was to determine the contribution of food safety control to consumer protection by the example of Ukraine and the experience of some foreign countries. The article covers the following issues: the current state of food security in Ukraine and some foreign countries; weaknesses and strengths of the national food control system and discussion of possible ways to improve; the most important regulatory decisions in the field of food safety and consumer protection; reforming the national food control system and developing general recommendations for the formation of an effective national food control system. The object of research is the institutional component of food safety control.